Marine N2O cycling from high spatial resolution concentration, stable isotopic and isotopomer measurements along a meridional transect in the eastern Pacific Ocean - Bourbonnais, Annie; Chang, Bonnie X.; Sonnerup, Rolf E.; Doney, Scott C.; Altabet, Mark A. (Frontiers in Marine Science, 2023)
Nitrous oxide (N2O) is a potent greenhouse gas and ozone depleting substance, with the ocean accounting for about one third of global emissions. In marine environments, a significant amount of N2O is produced by biological processes in Oxygen Deficient Zones (ODZs). While recent technological advances are making surface N2O concentration more available, high temporal and spatial resolution water-column N2O concentration data are relatively scarce, limiting global N2O ocean models’ predictive capability. We present a N2O concentration, stable isotopic composition and isotopomer dataset of unprecedently large spatial coverage and depth resolution in the broader Pacific, crossing both the eastern tropical South and North Pacific Ocean ODZs collected as part of the GO-SHIP P18 repeat hydrography program in 2016/2017. We complement these data with dissolved gases (nitrogen, oxygen, argon) and nitrate isotope data to investigate the pathways controlling N2O production in relation to apparent oxygen utilization and fixed nitrogen loss. N2O yield significantly increased under low oxygen conditions near the ODZs. Keeling plot analysis revealed different N2O sources above the ODZs under different oxygen regimes. Our stable isotopic data and relationships between the N2O added by microbial processes (ΔN2O) and dissolved inorganic nitrogen (DIN) deficit confirm increased N2O production by denitrification under low oxygen conditions near the oxycline where the largest N2O accumulations were observed. The slope for δ18O-N2O versus site preference (SP, the difference between the central (α) and outer (β) N atoms in the linear N2O molecule) in the eastern tropical North Pacific ODZ was lower than expected for pure N2O reduction, likely because of the observed decrease in δ15Nβ. This trend is consistent with prior ODZ studies and attributed to concurrent production of N2O from nitrite with a low δ15N or denitrification with a SP >0‰. We estimated apparent isotope effects for N2O consumption in the ETNP ODZ of 3.6‰ for 15Nbulk, 9.4‰ for 15Nα, -2.3‰ for 15Nβ, 12.0‰ for 18O, and 11.7‰ for SP. These values were generally within ranges previously reported for previous laboratory and field experiments.